Profil Kadar Kortisol dan Seng pada Kambing Peranakan Etawah Saat Melahirkan yang Diberi Tambahan Seng dalam Pakannya - Derthi Widhyari, Sus; Widodo, Setyo; Teguh Wibawan, I Wayan; Sutama, I Ketut; Esfandiari, Anita (Jurnal Veteriner, 2012)
The objective at this experiment was to study the role of zinc supplementation (Zn) in minimizingstress at parturition. Thirty etawah cross breed age 3-6 years with average body weight 30-50 kg were usedin this study and divided into three groups ; i) animal were given grass + feed concentrate + ZnSO4 40 mg/kg dry matter ( control group) ; (ii) grass + feed concentrate + ZnSO4 60 mg/kg dry matter (treatment 1), and(iii) grass + feed concentrate + ZnSO4 80 mg/kg dry matter (treatment 2), respectively drinking water weregiven ad libitum. To monitor zinc and cortisone level, blood samples were withdrawn from each animalevery two weeks starting at age of pregnancy 3 months up to two months post parturition, in addition, tomonitor the cortisone level blood samples were also collected at 1,2,3 and 7 days post parturition. The Znand cortisone serum were analyzed using atomic absorbent spectro photometric (AAS) andradioimmunoassay (RIA), respectively the result showed that generally pregnancy at the beginning andget serum level at cortisone was relatively similar between the three animal groups and there was atendency to increase and reached peak at parts then gradually decrease until the and of the observation. Atparturition the lowest serum level at cortisone (19.00±18.72 mg/ml) was observed in animals receiving the60/ dry matter zinc supplement compared to animal receiving 80 mg/ dry matter zinc ( 52.65 ± 30.83 mg/ml) and control animal ( 75.92 ± 42.88 mg/ml). in addition serum level at Zn was significantly higher inanimal receiving 60 mg and 80 mg Zn in their diets compared to control animals. The best profiles wereseen in animal given 60 mg/kg dry matter Zn supplement. In conclusion, the addition of Zn in the diets hadsignificant effect in minimizing stress as pictured by the low serum level at cortisone at parturition.
Keywords: zinc, cortisol, parturition period, peranakan Etawah goats